2017
DOI: 10.1149/2.0511704jes
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Electroextractions of Ce and Nd from LiCl-KCl Molten Salt Using Liquid Ga Electrode

Abstract: The aim of this work is to explore the electroextractions and related thermodynamic properties of Ln (Ce and Nd) as actinide surrogates on the liquid Ga media, aiming at further Ln/An separation. The activities, activity coefficients and solubilities of Ce and Nd in the liquid Ga media were determined by open circuit potential at the temperature range from 698 to 798 K. The electroextractions of Ce and Nd and their corresponding current efficiencies on a static liquid Ga electrode were investigated by gavanost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Figure 11 exhibits a micrograph of the surface of a thin layer of the electrolyte adherent to the Mo cathode, obtained after 3600 s of potentiostatic deposition. The XRD analysis revealed that the black layer, which was closely attached to the Mo WE, consists entirely of NdF2 and NdF3 in accordance with Equation (14). In order to downgrade the influence of the disproportionation on the Nd electrodeposition yield efficiency, metal neodymium is sometimes added to the electrolyte to replace the freshly deposited Nd in the reaction Equation 14 There is also one identifying Nd metal on Mo substrate obtained by galvanostatic electrodeposition [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 11 exhibits a micrograph of the surface of a thin layer of the electrolyte adherent to the Mo cathode, obtained after 3600 s of potentiostatic deposition. The XRD analysis revealed that the black layer, which was closely attached to the Mo WE, consists entirely of NdF2 and NdF3 in accordance with Equation (14). In order to downgrade the influence of the disproportionation on the Nd electrodeposition yield efficiency, metal neodymium is sometimes added to the electrolyte to replace the freshly deposited Nd in the reaction Equation 14 There is also one identifying Nd metal on Mo substrate obtained by galvanostatic electrodeposition [26].…”
Section: Resultsmentioning
confidence: 99%
“…Commonly investigated salt combinations include chlorides, fluorides, and oxides of alkali and alkaline earth metals and neodymium [8,10,11]. The electrolytes made of molten chlorides are mainly composed of NdCl 3 + LiCl + KCl [1][2][3]7,[11][12][13][14][15][16]. Fluoride electrolytes are considered more suitable because of their higher conductivity, lower hygroscopy, and higher current efficiency of the neodymium deposition compared to the chloride melts [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In Nd electro-extraction, Liu et al employed a liquid gallium (Ga) electrode to suppress multistage redox transitions so as to obtain high current efficiencies. 18 In their work, it was demonstrated that the Nd electrodeposition on liquid Ga underwent a one-step reduction to Nd metal, implying that no soluble intermediates (which typically lower the efficiency by diffusing away from the electrode) were generated. Through such an approach, current efficiency exceeding 90% was achieved; however, the electrodeposited Nd was observed to form an alloy with the Ga electrode.…”
mentioning
confidence: 99%
“…27,28 Therefore, it is critical to recover and separate lanthanides from molten salt for nuclear fuel cycle and the purification of waste salts. 29 In recent years, the electrorecovery lanthanides from molten salt were explored on various electrodes, for example, Mg, 30 Al, [31][32][33][34] Ni, 35,36 Cu, [37][38][39] Bi, [40][41][42][43] Zn, 38,39,44,45 Cd, 46,47 Sn, 48 Pb, [49][50][51] and Ga. 52 Since there are some advantages to use low melting point metal as a liquid working electrode, many researchers paid more attentions to the electrochemical extraction using a liquid electrode. Our group investigated the electroextraction of Tb and Y from molten chloride using solid Cu and liquid Zn as working electrodes and found that under same conditions, metallic Y and Tb easily deposited on liquid Zn electrode.…”
Section: Introductionmentioning
confidence: 99%